2010
DOI: 10.2165/11530190-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Dermatology Publications over the Past 15 Years

Abstract: The fields of pediatric and adult dermatology have had a significant yearly increase in studies providing a high level of scientific evidence with a much slower rise in the number of articles providing a lower level of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 6 publications
1
14
1
1
Order By: Relevance
“…It has been reported that the number of publications in dermatology has been increasing year by year. 13,14 In the present study, we demonstrate that there has also been a dramatic increase in the number of publications in dermatology in mainland China. The dramatic increase in publications in mainland China could be partially attributable to its rapid economic growth.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…It has been reported that the number of publications in dermatology has been increasing year by year. 13,14 In the present study, we demonstrate that there has also been a dramatic increase in the number of publications in dermatology in mainland China. The dramatic increase in publications in mainland China could be partially attributable to its rapid economic growth.…”
Section: Discussionsupporting
confidence: 58%
“…It has been reported that the number of publications in dermatology has been increasing year by year 8,9 . In the present study, we demonstrate that there also has been a dramatic increase in the number of publications in dermatology in mainland China.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatology in Japan, the well-developed country, published papers more than the total of mainland China and South Korea over the last 10 years. It is reported that the number of publications in dermatology has been increasing yearly in both developing and developed countries [6,16] and the increase in the number of publications is associated with improvement of economic conditions [1,6,17]. In contrast, the present study revealed that the number of publications in dermatology in Japan remained unchanged from 2003 to 2012 despite the linearly increase of GDPPC.…”
Section: Discussioncontrasting
confidence: 74%
“…Our search was limited to human subjects and to English language publications, and we sorted our results by PubMed publication type (ie, clinical trials, reviews, systematic reviews, meta-analyses, editorials, letters, case reports, practice guidelines, and historic articles). The PubMed engine has previously been found to accurately determine the publication type 100% of the time [1,2,6,7]. In order to verify and validate the accuracy of the publication type in the present study, we drew a random sample of 10 articles from 5 randomly selected years for manual evaluation.…”
Section: Methodsmentioning
confidence: 99%